The sinner. Season two [videorecording (DVD)] - Biel, Jessica, 1982-; Abbott, Christopher, 1986-; Norwood, Dohn (Universal Pictures Home Entertainment, 2018)
Following the murder of a couple by their eleven-year old son, Detective Harry Ambrose returns to his hometown in rural New York to assess the unsettling and heart wrenching crime. He finds himself pitted against those who'll stop at nothing to protect its secrets.